Influence of Clinical Markers of Dopaminergic Behaviors on Depressive Symptoms During Withdrawal in Cocaine Users - Cabé, Julien; Brousse, Georges; Pereira, Bruno; Cabé, Nicolas; Karsinti, Emily; Zerdazi, El-Hadi; Icick, Romain; Llorca, Pierre M.; Bloch, Vanessa; Vorspan, Florence; De Chazeron, Ingrid (Frontiers in Psychiatry, 2021)
Background During cocaine withdrawal, transient depressive symptoms that do not meet the criteria for depression, but promote relapse, are frequently observed. Their temporality could evoke a role of dopamine, especially since the underlying mechanism of this depressive symptoms is not well understood. We hypothesized that variation in the dopaminergic activity profile, modeled from clinical markers, could be implicated in the development of depressive symptoms during cocaine withdrawal. Methods We compared patients reporting depressive symptoms (RDS+) or not (RDS-) during cocaine withdrawal. We evaluated dopaminergic activity through indirect clinical markers based on the known dopaminergic behaviors. A combined criterion was constructed for hyper and hypo dopaminergic models according to the O’Brien method and illustrated by the Hedges’ effect-size and forest-plot graph. A multidimensional factorial analysis was carried out to determine which parameters discriminate RDS+/RDS- patients. Results 313 patients were included, and 77% had depressive symptoms during cocaine withdrawal. Hyperdopaminergic variables used to discriminate the two groups had a large overall effect size (-0.669) and included psychotic symptoms (-0.524), hallucinations (-0.548), and delusions (-0.528). The overall effect of the hypodopaminergic component was considerable (-0.604) with a large effect size for the severity of dependence (-0.616), withdrawal symptoms (-0.578), and anhedonia (-0.528). The combined model including hyperdopaminergic and hypodopaminergic components had the largest effect size (-0.785). Conclusion The dopaminergic activities profile, assessed by indirect clinical markers, seems to characterize patients with depressive symptoms very well during cocaine withdrawal. RDS+ patients reported moreover higher levels of psychotic symptoms and more severe cocaine use disorder than RDS-.